A comprehensive transcriptomic analysis of differentiating embryonic stem cells in response to the overexpression of Mesogenin 1 - Liu, Dahai (Aging (Albany NY), 2016)
The mutation of somitogenesis protein Mesogenin 1 (Msgn1) has been widely used to study the direct link between somitogenesis and the development of an embryo. Several studies have used gene expression profiling of somitogenesis to identify the key genes in the process, but few have focused on the pathways involved and the coexpression patterns of associated pathways. Here we employed time-course microarray datasets of differentiating embryonic stem cells by overexpressing the transcription factor Msgn1 from the public database library of Gene Expression Omnibus (GEO). Then we applied gene set enrichment analysis (GSEA) to the datasets and performed candidate transcription factors selection. As a result, several significantly regulated pathways and transcription factors (TFs), as well as some of the specific signaling pathways, were identified during somitogenesis under Msgn1 overexpression, most of which had not been reported previously. Finally, significant core genes such as Hes1 and Notch1 as well as some of the TFs such as PPARs and FOXs were identified to construct coexpression networks of related pathways, the expression patterns of which had been validated by our following quantitative real-time PCR (qRT-PCR). The results of our study may help us better understand the molecular mechanisms of somitogenesis in mice at the genome-wide level.